Low-Cost Carrier Passenger Repurchase Intention: A Structural Equation Model Analysis - Vuthisopon, Sujira (Animo Repository, 2017)
Low-cost carrier (LCC) aviation has exploded globally, which now represents 26% of all passenger seats, while in Southeast Asia LCC passengers have soared to 54%. The purpose of this research was, therefore, to develop and examine the accuracy of a structural equation model of the factors affecting repurchase intention of low-cost carrier passengers in Thailand. Convenience sampling was utilized to obtain a sample of 440 individuals from four Thai low-cost carriers, including Thai AirAsia, Nok Air, Thai Lion Air (Don Muang Airport-DMK), and Thai Smile Airways (Suvarnabhumi Airport-BKK) in 2016. To examine the study’s five latent and 22 observed variables, a 97-item survey was used. Results from the study determined the positive and significant influences that customer satisfaction has on customer loyalty, followed by electronic service quality on customer satisfaction, and customer satisfaction on repurchase intention, respectively.